Quality of Information for Skin Cancer Prevention: A Quantitative Evaluation of Internet Offerings - Uter, Wolfgang; Eversbusch, Christina; Gefeller, Olaf; Pfahlberg, Annette (Healthcare, 2021)
(1) Background: Different sources of information are used by the population regarding skin cancer prevention. The pertinent quality of information that can be retrieved via an internet search engine needs assessment; (2) Methods: Four topical searches in common language were entered into Google (TM). The first 200 "hits" were stored for further use. Eligible websites were evaluated using content-based criteria based on the current German medical guideline "Skin cancer prevention" and employing generic (DISCERN, HONcode) quality criteria. (3) Results: Overlap between the four search results was between 0 and 7 of 200. The completeness of relevant content was scored with a median of 10 points (first quartile (Q1):6; Q3:14) and thus, it was much lower than the theoretical maximum of 43 points. Global quality, with a maximum of 10 points, was 3 in median (Q1:2; Q3:4). Quality and completeness, respectively, were somewhat higher in the higher ranks of search results. The generic quality was moderate. (4) Conclusions: A direct comparison with other sources of information (print, audio-visual, presentation, or personal counselling) is not possible, but important deficits concerning the quality and scope of relevant information on the internet are demonstrated.
CRIS-Team WoS Importer:2021-03-12